Lignin-assisted solid-phase synthesis of nano-CuO for a photocatalyst with excellent catalytic activity and high performance supercapacitor electrodes. Issue 70 (11th July 2016) - Wang, Xiaohong; Wu, Fangsheng; Duan, Yawei; Wang, Yingying; Hao, Chen; Ge, Cunwang
Abstract : CuO nanostructures were successfully synthesized using NaOH and Cu(NO3 )2 as starting materials by an aminated lignin (AL)-assisted solid-phase method. Abstract : CuO nanostructures were successfully synthesized using NaOH and Cu(NO3 )2 as starting materials by an aminated lignin (AL)-assisted solid-phase method. The results of X-ray diffraction (XRD) analyses indicate that the prepared CuO nanoparticles have a monoclinic crystal structure with an abundance of mesopores. The emission scanning electron microscopy (SEM) images exhibit noticeable changes in morphology and size of the CuO samples with different content of AL. The CuO nanostructures were applied into the photocatalytic degradation of methylene blue (MB) and methyl orange (MO) under UV light irradiation. Meanwhile, the best photocatalytic activity with an AL dosage of 0.5 g and the calcination temperature at 400 °C shows almost complete degradation (∼97.83%) for MB and 66.76% for MO under UV light irradiation for 1.5 h, respectively. The supercapacitor behavior was characterized by cyclic voltammetry, galvanostatic charge–discharge and electrochemical impedance spectroscopy techniques. The maximum specific capacitances of CA3.0-400 are found to be 644.8 F g −1, much higher than other samples. However, it exhibits slightly worse cyclic stability compared with CA0.5-400.